Industrial training job matching web application system / Muhammad Hanif Zurlani - Zurlani, Muhammad Hanif (2014)
The problem faced by students in the current process of applying for industrial training is finding the appropriate organizations that matches their skills and attributes. This system will manage the process of matching the students to the appropriate organizations and vice versa and rank them accordingly in a more effective and efficient ways. The objectives of this research are to identify the user requirements, to develop the prototype and demonstrate the ITJM system. The first objective was achieved by doing interviews, web observation and collecting and reviewing secondary data. All the requirements gathered were then compiled and summarized. Rapid Application Development (RAD) methodology was used which ensured smooth progress throughout the system development from requirements gathering up until the system was tested. ITJM is a web-based system and was developed using Adobe Dreamweaver CS6, Xampp which acts as the web server and MySQL as the database platform using PHP as the scripting language.